2021
DOI: 10.1002/lary.29969
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of Online Support Community Participation Among Patients With Vestibular Disorders

Abstract: Objectives/Hypothesis: To formally document online support community (OSC) use among patients with vestibular symptoms and gain an appreciation for the perceived influence of participation on psychosocial outcomes and the impact on medical decision-making.Study Design: Self reported internet-based questionnaire.Methods: The Facebook search function was paired with a comprehensive list of vestibular diagnoses to systematically collect publicly available information on vestibular OSCs. Next, a survey was designe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 44 publications
(103 reference statements)
0
19
0
Order By: Relevance
“…Moreover, only text data were analyzed in seven studies (e.g., Twitter tweets, Facebook posts, and blog posts), followed by video and text data in five studies, and only video data in four studies. The remaining studies analyzed self-reported questionnaire data (Manchaiah et al, 2020b;Manchaiah et al, 2020b;Vanstrum et al, 2021). <<Table 2 near here>>…”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, only text data were analyzed in seven studies (e.g., Twitter tweets, Facebook posts, and blog posts), followed by video and text data in five studies, and only video data in four studies. The remaining studies analyzed self-reported questionnaire data (Manchaiah et al, 2020b;Manchaiah et al, 2020b;Vanstrum et al, 2021). <<Table 2 near here>>…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Such techniques may aid in the understanding of results amongst hearing healthcare professionals as they are familiar with qualitative analysis techniques. The remaining studies that conducted surveys performed quantitative analyses by using descriptive statistics to examine survey responses (Manchaiah et al, 2020b;Manchaiah et al, 2020d;Vanstrum et al, 2021).…”
Section: Description Of the Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations